(untitled) (Trabalho & Educação, 2018)
Workers that looking for CEFET-MG to capacitate yourselves in activities relative to construction site, most them are construction workers, participated in focal groups used in this research, whose objective was to understand their school and family lives and their professional perspectives revealed that, nevertheless the familiar efforts to keep them in school at poor conditions that they lived while youth have had strong contribution to them leave early the school to begin at construction site in building area. These workers think that your actual conditions in working class happened because they had no opportunity or had failure by the fact of them poor conditions it took them a school failure. Faraway of some personal failure feeling, they are back to school in adulthood and say to yourselves that are able; these persons are looking for a better social placement and a better placement in the labor market and have expectations to continue their studies, including Higher Education. ___ Os trabalhadores que procuram o CEFET-MG para capacitarem-se em atividades de canteiros de obras, a maioria da construção civil, ao participarem dos grupos focais utilizados nesta pesquisa, cujo objetivo era compreender suas vidas escolares e familiares e suas perspectivas profissionais revelaram que, não obstante o esforço familiar para mantê-los na escola, as condições precárias nas quais se encontravam quando jovens contribuíram fortemente para uma trajetória escolar marcada por rupturas e abandonos, que os empurraram precocemente para os canteiros de obras da construção civil. Para eles, a condição operária na qual se encontram se deve muito mais a uma ausência de oportunidades ou a um fracasso da situação na qual viviam do que, propriamente, a um fracasso escolar. Distantes de qualquer sentimento de fracasso, eles retornam à escola depois de adultos, se dizem intelectualmente capazes e, visando melhor se posicionarem socialmente e no mercado de trabalho, alimentam expectativas de dar continuidade aos estudos, inclusive em nível superior.